Cost Estimation Analysis of Construction Projects on Simple Earthquake-Resistant Houses - Rahman Arifin, Ari Syaiful; Jonrinaldi, Jonrinaldi (Universitas Negeri Padang, 2024)
Earthquakes are natural disasters that often hit Indonesia, causing various losses in human life, including damage to homes and places to live. Therefore, the importance of building earthquake-resistant houses cannot be ignored. The research aims to obtain a comparison of the estimated cost of a type 36 simple house construction project, by considering the comparison between conventional structures and structures that are strengthened to resist earthquakes. The data used involves working drawings, technical specifications, and work unit price analysis (AHSP) based on PUPR Ministerial Regulation No. 8 of 2023 and a list of unit prices for wages and materials for work in the Public Works and HSBGN sector for the 2022 fiscal year in the city of Padang. The cost estimation results show that for a simple house with a conventional structure, the construction cost is IDR 243,000,000, while for a simple house with earthquake-resistant reinforcement, the cost reaches IDR 251,800,000. This additional cost was caused by strengthening work on foundations, columns and beams, walls, and trusses. Even though there was an increase in costs of around 3.63%, this result can be a consideration for the community. It is important to realize that with relatively small additional costs, people can increase safety and comfort in building construction. The results of this research can be a strong basis for stakeholders in the construction and policy fields to consider safety and comfort as the main factors in developing housing infrastructure.